Impact of Financial Management Practices on Poverty Reduction among Young Adults in Low-Income Communities in Lagos State, Nigeria - Yinusa, O.; Olowu, A. (Journal of Research in Adult and Continuing Education, 2025)
This study examines the effects of financial management practices on poverty reduction among young adults in low-income communities in Lagos State, Nigeria. Two research questions and two hypotheses were raised and tested to guide this study Employing a descriptive research design, the research targets young adults aged 18–35, with a sample of 385 participants selected using multi-stage sampling including, stratified proportional sampling from four communities: Epe, Ikorodu, Oshodi, and Badagry. Data were collected through a structured questionnaire. Frequency tables, mean scores, Pearson product moment correlation and simple linear regression were used to analysed the data. The analysis revealed a significant lack of financial literacy, with many participants struggling to engage in effective budgeting and saving practices, contributing to their vulnerability to poverty and limiting access to basic necessities such as food, education, shelter, and healthcare. Findings indicate that effective budgeting and proactive saving habits are directly correlated with improved access to essential resources. Based on these findings, the study recommends that stakeholders including the Nigerian government, financial institutions, and NGOs enhance financial literacy programmes and improve access to financial services to empower young adults and equip them with the skills to make informed decisions, ultimately supporting poverty reduction in Lagos State.
Keywords: Financial literacy; Young adults; Financial management practice; Poverty reduction